The Relationship Between Dimensions of the Family Quality Index Provincial Level Throughout Indonesia in 2021 - Puspitawati, Herien; Sarma, Ma'mun; Sutarman, Deddy Cahyadi; Septiana, Maya; Cahayani, Octaria Intan (Journal of Family Sciences, 2023)
The Family Quality Index (IKK) measures the success of family development in Indonesia, and can be used as a basis for planning and indicators of successful family development at the central, provincial/regional, and regency/city levels. The objectives of the study were to analyze (1) the Cronbach’s alpha reliability test and the content validity of IKK indicators, (2) the achievements of IKK at the provincial and national levels, and (3) the relationship between indicators and dimensions of IKK. The research method is a quantitative analysis of BPS secondary data for 2021. Cronbach’s alpha was 0.50, and content validity was between 0.03 and 0.77. The provincial IKK score in 2021 range from 65.16 to 76.80, with a national achievement score of 73.43. Three provinces were included in category 3, namely "quality of gender-responsive families" and 31 other provinces were included in category 2, namely "quality of sufficiently gender-responsive families.” There were positive relationships between the dimensions of structural legality and socio-psychological resilience and between the dimensions of structural legality and sociocultural resilience. Furthermore, there were positive relationships between the dimensions of physical resilience and economic resilience, and between the dimensions of physical resilience and sociocultural resilience. The research implications showed that the potential problems of families at the provincial level were used as inputs in preparing action plans at the national and provincial levels.